Climate Psychology: What is preventing the uptake in lifestyle changes that would significantly reduce one’s environmental impact? - Macdonald, Chris (Open Science Journal, 2020)
Human consumption and human emissions are rapidly destroying our home planet and the vital ingredients of life—the science is clear and abundant. And so, we need to make extreme changes in many aspects of life as quickly as possible—as a matter of survival. This paper explores the underlying mechanisms that prevent the public from making lifestyle changes that would significantly reduce their environmental impact. As part of the experiment, students were asked to complete the same anonymous survey. Before starting they were reminded that there is no right or wrong answer and that they should give their honest opinion. Perhaps the most reassuring of the findings was that over 90% of both UK and U.S. participants stated that they were concerned about the climate crisis and that they felt that it is important to make lifestyle changes to reduce harmful emissions, thus indicating a general awareness and motivation to take personal action. The most common reasons cited for not wanting to make a suggested lifestyle change were that the participant felt as though it is difficult to make the suggested change, and that the participant felt that the suggested change would not make a significant difference. Accordingly, the opposite statements were the most common reasons given for why the participants would consider making a suggested lifestyle change (it is easy to make the suggested change, and the participant felt that the suggested change would make a significant positive impact). The paper concludes by offering some ways in which we could facilitate the uptake in sustainable lifestyle choices.